Efficiency of hydrolysis of whey protein serine proteases - Петюх, Г.П.; Романова, Н.А.; Гаркава, К.М. (Proceedings of National Aviation University (archive), 2009)
Research of relative enzymatic whey protein isolate (WPI) hydrolysis efficiency was conducted. Seven enzymes in three concentrations by pH 7.0 t=50°C were used. The most efficient showed to be Protease R in concentration 0,0002 g/ml.